Breast cancer: role of psychological support and the effectiveness of treatment - A. V. Vazhenin; D. A. Tsiring; M. N. Mironchenko; I. V. Ponomareva; E. A. Evstafeeva (Сибирский онкологический журнал)
Background. Breast cancer is the most frequently diagnosed and life-threatening cancer in women worldwide. Since the disease diagnosis and treatment have improved greatly over time, quality of life has become an important outcome measure in breast cancer clinical investigations. The goal of the study was to analyze quality of life in women with breast cancer and to conduct a meta-analysis of data indicating the need for psychological support aimed at improving the quality of life in breast cancer patients. Material and methods. The study involved 186 women who were diagnosed with breast cancer no earlier than 6 months from the date of the survey. All patients had a luminal type of tumor. To study the quality of life of women with breast cancer, the sf-36 (36-item short-Form Health survey) questionnaire recommended by the international protocol was used. Results. Comparative analysis of standardized indicators of the quality of life indicats that the quality of life of women with breast cancer is significantly lower than that of women from the population (p<0.05). This result requires attention from both social/psychological services and physicians, due to the fact that the general indicator of the quality of life is associated with the prognosis of survival. The essence of providing psychological support to women with breast cancer is not only to alleviate their moral and psychological suffering, but also to enhance the effect of treatment and, as a result, increase survival. The authors come to the conclusion that it is necessary to include psychological rehabilitation programs in the protocol for treating women with breast cancer to enhance the effect of treatment, improve the quality of life.